(untitled) (Research, Society and Development, 2024)
Introduction: Dipyrone is a drug derived from pyrazolone. Due to its analgesic and antipyretic effects, it has become widely used in Brazil and is among the ten most widely marketed drugs. Its association with agranulocytosis has been recognized since 1970, with a mortality rate of between 10 and 16%. Objective and Methodology: This case report presents a clinical case of agranulocytosis secondary to re-exposure to dipyrone with a suggestive clinical and laboratory picture. Conclusion: Anamnesis plays a crucial role in establishing the temporal relationship between the use of the drug and the appearance of signs and symptoms, with an impact on early diagnosis and appropriate therapeutic management for the patient’s prognosis.